康柏斯涂料（中国）有限公司未来战略选择 = The strategy management selection of KPS for its future development - 蔡掁禹Choy, Chin Yee (2008)
Set up the strategy management selection frame for KPS and make it more adapted to environment, competent, and keeping a sustaining development by introducing classifies and composition of the development strategy to support the further research on KPS.